Light Control Using Human Body Temperature Based on Arduino Uno and PIR (Passive Infrared Receiver) Sensor - Perkasa, Reza; Wahyuni, Refni; Melyanti, Rika; -, Herianto; Irawan, Yuda (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to implement the PIR sensor, Arduino UNO and 2 channel relay Module to automatically turn on the lights in the classroom at the STMIK Hang Tuah Pekanbaru campus, where the classes at the Hang Tuah Pekanbaru STMIK campus still use manual switches as controllers lights on. Therefore, a device is designed that can control the lights by using movements detected by the PIR sensor and processed using a computer.This system functions to turn on the lights automatically when someone enters the classroom and turn off the lights automatically when no one is in the class. The hardware used is Arduino Uno microcontroller, PIR motion sensor, 2 channel relay module, and 1.5 volt flashlight. The software for making programs is Arduino IDE where the programming language used is the C programming language. The test results show that the PIR sensor can detect the movement of people entering or leaving a room.